Assessing ecological environmental quality and conservation effectiveness in the World’s largest urban green heart using the remote sensing ecological index (RSEI) and propensity score matching (PSM) - Wu, Chongbo; Liu, Huanyao; Meng, Cen; Li, Xiaoma; Gan, Dexin (Frontiers in Environmental Science, 2025)
Urban Green Hearts (GHs) represent a unique ecological protection measure or policy. Evaluating the spatiotemporal dynamics of the ecological environmental quality (EEQ) of urban GHs and revealing their conservation effectiveness is crucial for promoting the coordination between regional development and environmental preservation. This study examines the Changsha-Zhuzhou-Xiangtan urban agglomeration Green Heart (CZT-GH) and its 3 km buffer zone, evaluating the effectiveness of ecological environment protection following GH policy implementation, and analyzing the spatiotemporal dynamics of EEQ. The Remote Sensing Ecological Index (RSEI) was calculated using the Google Earth Engine (GEE) platform, and conservation effectiveness was evaluated through Propensity Score Matching (PSM) and Wilcoxon tests. The findings reveal that: (1) The RSEI demonstrated an average annual growth rate of 0.0038 years-1 over 31 years, with significant increases during 1990–2013 (0.0045 years-1) and 2013–2020 (0.0089 years-1). (2) Comparing pre- and post-GH policy implementation periods (1990–2013 vs. 2013–2020), areas showing EEQ improvement increased from 77.15% to 89.69%, while areas with stable and decreased EEQ declined from 22.36% to 10.17%. (3) GH policy demonstrates substantial positive conservation effects, with both GH and the 3 km buffer zone exhibiting EEQ improvements. This research provides valuable insights for GH management strategies and enhancing the balance between regional development and environmental preservation.